Toxicity of a methotrexate metronomic schedule in Wistar rats - Correal, María Lucía [UNESP]; Camplesi, Annelise Carla [UNESP]; Anai, Letícia Abrahão [UNESP]; Bertolo, Paulo Henrique Leal [UNESP]; Vasconcelos, Rosemeri de Oliveira [UNESP]; Santana, Áureo Evangelista [UNESP] (Elsevier, 2020)
Metronomic chemotherapy is a relevant strategy that uses low doses of antineoplastic drugs for sustained periods to control tumor growth, an alternative frequently utilized in veterinary patients. This work aimed to evaluate the toxic effects of a metronomic oral dose of methotrexate (MTX) for 45 days in tumor-free Wistar rats when compared with control animals. Clinical alterations, body weight, food, and water intake were monitored daily, and bone marrow suppression, hematological, biochemical, and histopathological analyses were performed at three points (days 30, 45, and 60). MTX-treated animals did not demonstrate severe systemic involvement. At 30 days, compared with control animals, MTX-treated animals showed significant leukocytosis (11.9 ± 2.3 vs. 7.8 ± 0.2 106/μL; P <.05) and augmentation of immature myeloid populations from bone marrow (9.0 ± 0.8 vs. 6.5 ± 1.5%; P <.05), and at 60 days, treated animals showed significant neutrophilia (35.0 ± 11.0 vs. 23.00 ± 3.0%; P <.05), depletion of bone marrow lymphocytes (8.2 ± 0.7 vs. 11.5 ± 1.9%; P <.05), and immature myeloid populations (7.2 ± 0.7 vs. 8.3 ± 0.6%; P <.05). At a histopathological level, splenic hypoplasia and respiratory inflammatory lesions were significant when compared with control animals, presenting mild to moderate myelotoxicity, immune suppression, and associated clinical compromise that persisted beyond treatment withdrawal. This suggested that MTX metronomic toxicity should not be neglected owing to the observed residual side-effects and special care should be taken regarding myelosuppression.
Keywords: Animals; Anti-folate; Cancer; Chemotherapy; Metronomic